Catalogue of the Krantz Brachiopod Collection at the Science Museum of the University of Coimbra (Portugal) - Schemm-Gregory, Mena; Henriques, Maria Helena (Zootaxa, 2013)
The specimens of the Krantz Brachiopod Collection of the Science Museum of the University of Coimbra (Portugal) are revised according to modern taxonomy and presented in systematic order according to inventory number, type species, figured representative and, as far as possible, detailed information regarding stratigraphy and collecting localities. The collection itself contains 170 lots yielding 474 specimens and representing 15 of the 27 brachiopod orders. The material comes from Europe, Russia, and the United States and represents all Palaeozoic and Mesozoic periods; the majority of the brachiopods are from the Devonian of Germany, mostly collected in classical outcrops from the Rhenish Slate Mountains, many of which are no longer accessible.